Design Development Research Approach in Developing Gel Electrophoresis Virtual Laboratory to substitute Real Practicum - Yuyun Maryuningsih; Budi Manfaat; Riandi Riandi; Nuryani Rustaman (Scientiae Educatia: Jurnal Pendidikan Sains, 2019)
One of the purposes of Genetic practicum is that students can understand DNA separation techniques, by conducting gel electrophoresis practicum. Some Institutions of Teacher Training (LPTK) have problems in gel electrophoresis practicum due to unavailability of the lab. For this reason, it is necessary to try a replacement practicum in the form of a virtual laboratory to meet practicum objectives. This research uses a design development research (DDR) approach, through six stages, namely 1) identifying problems by determining indicators of learning and supporting literature studies, 2) determining the purpose, 3) designing and developing devices by designing virtual laboratories, determining the software that will be used, compiling a virtual laboratory storyboard and expert validation, 4) testing, 5) evaluating the results of the trial, and 6) communicating the results of the trial. The validated device was tested on a limited basis on 38 student participants who took genetic practicum. Data on laboratory reports on virtual laboratory gel electrophoresis were analyzed descriptively based on the students' ability to understand gel electrophoresis. 95.89% of students have the ability to understand gel electrophoresis.